Marius the Epicurean $1 (BVolume 1s - Pater, Walter, 1839-1894 (Salt Lake City, UT : Project Gutenberg, 2003)
"Marius the Epicurean $1 (BVolume 1" by Walter Pater is a philosophical novel written between 1881 and 1884. Set in second-century Rome, it follows a young patrician's intellectual and spiritual journey through a time of uncertainty. Marius explores various philosophies$1 (Bfrom Epicureanism to Stoicism$1 (Bwhile encountering the emerging Christian faith. As he questions each system's ability to provide meaning, he moves from youthful hedonism toward something deeper, guided by friendship, beauty, and an elusive sense of peace he glimpses in unexpected places. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Marius_the_Epicurean
Release date is 2003-05-01
Alfred J. Drake. HTML version by Al Haines.
Keywords: Historical fiction; Bildungsromans; Young men -- Fiction; Christian fiction; Rome -- Fiction; Christianity and other religions -- Roman -- Fiction